Wildlife Responses to Climate Change : North American Case Studies - Edited By Stephen H. Schneider and Terry L. Root. (London Island Press, 2002)
This text presents the results of a project to research and study the impacts of global climate change on ecosystems and individual wildlife species in North America. Started in 1997, eight graduate students were provided with fellowships to conduct this research on global climate change
Includes Index, Maps and Illustrations.
Keywords: North America -- Climatic Changes -- Global Warming